DESIGNING USER EXPERIENCES IN CASUAL GAMES TO ENHANCE PRODUCT KNOWLEDGE - Eva Handriyantini; Stefanus Salem (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2025)
The widespread adoption of mobile platforms has transformed the gaming industry, making casual games highly popular due to their accessibility via smartphones and tablets. Beyond entertainment, casual games now serve as effective educational and marketing tools for delivering product knowledge. This study explores how user experience (UX) design can enhance product education in casual games by focusing on game mechanics, UX principles, narrative engagement, and product placement. Using a Design-Based Research (DBR) approach, this study develops, tests, and refines interactive experiences to ensure the effective implementation of design elements. Testing with 50 participants showed a 30% improvement in product recall after playing, along with high satisfaction levels regarding game usability and engagement. Participants also demonstrated improved time management skills and emotional connection to the game content. The game integrates challenges and activities designed to build cognitive and emotional engagement. Artificial intelligence (AI) technology is utilized through Unreal Engine to create a realistic and immersive environment. By incorporating product information into engaging gameplay, the game serves as both an educational and entertainment tool. This research provides practical insights for game developers, marketers, and educators on integrating educational content into casual games. By leveraging AI, user testing, and advanced UX strategies, casual games can become effective tools for game-based marketing and education. This game significantly enhances product knowledge retention, user engagement, and practical skills.